Hand hygiene knowledge, perception, and compliance among healthcare workers - Enty Tjoa; Cipta Mahendra; Suryanto Suryanto; Sandy Theresia; Marcella Wirjanata; Daniel Ardian Soeselo (Intelektual Pustaka Media Utama, 2022)
Healthcare-associated infections (HAIs) is a great issue to concern in healthcare services because it accounts for prolonged hospital stay and may lead to morbidity or mortality. Proper hand hygiene behavior in the healthcare environment is indispensable in minimizing the risk of HAIs. This study aimed to identify the impact of hand hygiene education on healthcare workers' (HCWs) compliance, knowledge, and perception of hand hygiene at Atma Jaya Hospital, Jakarta, Indonesia. The compliance of hand hygiene was evaluated using the World Health Organization’s (WHO) five moments for hand hygiene as the reference. Data on hand hygiene knowledge and perception were collected using a translated version of the WHO’s hand hygiene knowledge questionnaire and hand hygiene perception questionnaire, respectively. Results showed a significant increase in compliance with hand hygiene after the online session’s intervention had been implemented, except hand hygiene compliance for the ‘after touching patient surroundings’ moment. There was also a significant increase in the HCWs' hand hygiene knowledge after the intervention. The HCWs' perceptions are also found to be positive even before the intervention. This study concludes that the HCWs' knowledge and compliance with hand hygiene at Atma Jaya Hospital increase significantly after an educational intervention had been conducted.